(untitled) - J NDixit (New Delhi, India, 1998)
This book puts into perspective significant epoch-making events which profoudly affected the orientation of India's foreign policy priorities and also incisively analyses their ramification and repercussions. The book also examines international and intranational relations with reference to specific events
Keywords: india - foreign relations,india - history